Advantages and Disadvantages of Inclisiran: A Small Interfering Ribonucleic Acid Molecule Targeting PCSK9—A Narrative Review - Iveta Merćep; Nikolina Friščić; Dominik Strikić; Željko Reiner (Cardiovascular Therapeutics)
As dyslipidemias remain one of the main risk factors for developing cardiovascular disease, the question of maintaining optimal lipid levels with pharmacotherapy remains a subject of interest worldwide. In contrast to conventional pharmacotherapy, human monoclonal antibodies directed against proprotein convertase subtilisin/kexin type 9 (PSCK9) and small interfering RNA- (siRNA-) based drug targeting PCSK9 represent a new strategy for managing lipid disorders and reducing cardiovascular risk. Inclisiran is a long-acting, synthetic siRNA that targets hepatic production of PCSK9 and consequently causes a reduction in LDL-C concentrations by approximately 50% compared to placebo. The structural modification of inclisiran has led to better stability and prolonged biological activity of the drug. The main advantage over conventional pharmacotherapy and anti-PCSK9 monoclonal antibodies is its favorable administration regimen (0–90–180 days), which should lead to much better compliance. Clinical trials conducted so far have confirmed the tolerability and efficacy of inclisiran in long-term PCSK9 and LDL-C level reductions. Moreover, a short-term follow-up on the safety of inclisiran showed a relatively good safety profile of the drug. However, it is still of great importance for ongoing and forthcoming clinical trials to be continued on a larger group of patients in order to assess long-term tolerability, efficacy, and safety of inclisiran.